2012
DOI: 10.2105/ajph.2012.300702
|View full text |Cite
|
Sign up to set email alerts
|

Research on Discrimination and Health: An Exploratory Study of Unresolved Conceptual and Measurement Issues

Abstract: Objectives Our goal in this study was to better understand racial and socioeconomic status (SES) variations in experiences of racial and nonracial discrimination. Methods We used 1999 and 2000 data from the YES Health Study, which involved a community sample of 50 Black and 50 White respondents drawn from 4 neighborhoods categorized according to racial group (majority Black or majority White) and SES (≤ 150% or > 250% of the poverty line). Qualitative and quantitative analyses examined experiences of discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 30 publications
5
123
0
Order By: Relevance
“…Although multiple theories have been proposed to explain why African Americans would respond to discrimination with problem drinking, rarely have micro-longitudinal data been used to explore the daily processes that might give rise to this maladaptive behavior. The current study asserts that racial discrimination, a pernicious form of chronic stress commonly experienced by African Americans of all ages (McLaughlin et al, 2010;Seaton et al, 2008;Williams et al, 2012), may engender drinking problems by conferring a vulnerability for negativemood-related drinking. Alcohol consumption in response to negative moods, in turn, has been identified as an important predictor of alcohol problems independent of drinking levels (Cooper et al, 1995;Simons et al, 2005) and has been shown to have stronger associations with drinking problems among African Americans versus European Americans (Bradizza et al, 1999;Cooper et al, 1992).…”
mentioning
confidence: 83%
“…Although multiple theories have been proposed to explain why African Americans would respond to discrimination with problem drinking, rarely have micro-longitudinal data been used to explore the daily processes that might give rise to this maladaptive behavior. The current study asserts that racial discrimination, a pernicious form of chronic stress commonly experienced by African Americans of all ages (McLaughlin et al, 2010;Seaton et al, 2008;Williams et al, 2012), may engender drinking problems by conferring a vulnerability for negativemood-related drinking. Alcohol consumption in response to negative moods, in turn, has been identified as an important predictor of alcohol problems independent of drinking levels (Cooper et al, 1995;Simons et al, 2005) and has been shown to have stronger associations with drinking problems among African Americans versus European Americans (Bradizza et al, 1999;Cooper et al, 1992).…”
mentioning
confidence: 83%
“…Diverse ethnic groups are at a higher risk for chronic illnesses, have shorter life expectancies, and are less likely to receive vital preventative healthcare screenings (Agency for Healthcare Research and Quality, 2015;Richardson & Norris, 2010). As Williams et al (2012) note, low socioeconomic status, facing individual or institutional discrimination, and the stress of experiencing racial biases in health care further contribute to disparities in access to health care and treatment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceptual reasoning index which reflects one"s ability to think abstractly [29] and implies many meanings such as learning, planning, comprehending, imagination, making decisions, perception, and so on, did not predict extraversion. It has to be understood that intelligence is not restricted to only academic"s score and the ability to answer problems, but more of how a person is able to make use of their surroundings to their benefits with their intellect which differs for every person.…”
Section: Discussionmentioning
confidence: 84%